Respuesta :

Answer:

[tex]\displaystyle y= -\frac{3}{4} x + \frac{25}{4}[/tex].

Step-by-step explanation:

The equation of a circle of radius [tex]5[/tex] centered at [tex](0,0)[/tex] is:

[tex]x^{2} + y^{2} = 5^{2}[/tex].

[tex]x^{2} + y^{2} = 25[/tex].

Differentiate implicitly with respect to [tex]x[/tex] to find the slope of tangents to this circle.

[tex]\displaystyle \frac{d}{dx}[x^{2} + y^{2}] = \frac{d}{dx}[25][/tex]

[tex]\displaystyle \frac{d}{dx}(x^{2}) + \frac{d}{dx}(y^{2}) = 0[/tex].

Apply the power rule and the chain rule. Treat [tex]y[/tex] as a function of [tex]x[/tex], [tex]f(x)[/tex].

[tex]\displaystyle \frac{d}{dx}(x^{2}) + \frac{d}{dx}(f(x))^{2} = 0[/tex].

[tex]\displaystyle \frac{d}{dx}(2x) + \frac{d}{dx}(2f(x)\cdot f^{\prime}(x)) = 0[/tex].

That is:

[tex]\displaystyle \frac{d}{dx}(2x) + \frac{d}{dx}\left(2y \cdot \frac{dy}{dx}\right) = 0[/tex].

Solve this equation for [tex]\displaystyle \frac{dy}{dx}[/tex]:

[tex]\displaystyle \frac{dy}{dx} = -\frac{x}{y}[/tex].

The slope of the tangent to this circle at point [tex](3, 4)[/tex] will thus equal

[tex]\displaystyle \frac{dy}{dx} = -\frac{3}{4}[/tex].

Apply the slope-point of a line in a cartesian plane:

[tex]y - y_0 = m(x - x_0)[/tex], where

  • [tex]m[/tex] is the gradient of this line, and
  • [tex](x_0, y_0)[/tex] are the coordinates of a point on that line.

For the tangent line in this question:

  • [tex]\displaystyle m = -\frac{3}{4}[/tex],
  • [tex](x_0, y_0) = (3, 4)[/tex].

The equation of this tangent line will thus be:

[tex]\displaystyle y - 4 = -\frac{3}{4} (x - 3)[/tex].

That simplifies to

[tex]\displaystyle y= -\frac{3}{4} x + \frac{25}{4}[/tex].

Ver imagen jacob193